Perda de solo na bacia hidrográfica do Córrego Rico - SP, utilizando técnicas de geoprocessamento - Costa, Beatriz de Oliveira [UNESP] (2014)
The inappropriate use of watersheds without respecting the principles of conservation of its natural resources, causes devastation. The slopes of the watershed erosion process, one of the most significant forms of degradation, influenced by the management and use of unsuitable soil occurs. This study aimed to estimate soil losses in 1984 and 2011, in the Corrego Rico’s Watershed (CRW) using the Universal Soil Loss Equation (USLE) and propose alternatives that might mitigate the degradation in this area. Thematic maps of each factor of the equation were developed using GIS techniques and geographic information systems (GIS) programs. The erosivity factor (R) was higher in the region of Monte Alto with 7,984 MJ mm ha-1 h-1 year-1 (18.27% of BHCR) and lowest in Jaboticabal with 7,789 MJ mm h-1 ha-1 year-1 (46.33%). In erodibility (K) the highest value was 0.02838 th MJ-1 mm-1 ha of 13,001.40 Argilossolo Red Yellow and the lowest of 0.00608 th MJ-1 mm-1 in 22162.68 ha the Oxisol. For factor S is the largest area with embossed wavy 33,100.20 ha (57.06%) from 8.1 Slope and 20%. In factors Vegetation and Soil Management (C) and Conservation Practices (P) noted that in recent years there have been major changes such as the reduction of grazing areas and fruit and increased areas of cane sugar (55.83% in 1984 to 74.35% in 2011). A positive balance was increased vegetation cover of 1,993.95 ha in 1984 to 4,895.25 ha in 2011. The highest soil loss in the class of 21 and 50 t ha-1 year-1, occurred in an area of 15,226.00 ha (26.44%) in 1984 and 2011 between 11 and 15 t ha-1 year-1, an area of 17,297.91 t ha-1 year-1 (30.22%). The integrated use of USLE and GIS proved to be an effective technique in the spatial representation of soil loss in the basin of Rico Creek to identify the area’s most vulnerable to erosion and spatial-temporal variability